Quality of working life during the recession: the case of Croatia - Galić, Zvonimir (Array, 2012)
The quality of working life depends on the extent to which aspects of the job enable employees to satisfy important psychological needs. In this paper we describe two studies exploring the quality of working life in Croatia during the economic crisis that started in 2008. Within the first study, independent samples of employees recruited by psychology students were asked to self report quality of their jobs on four occasions between 2008 and 2010. In the second study, we tried to replicate the findings of the Study 1, using employees drawn from nationally representative samples of citizens between 2008 and 2011. Results of both studies showed that the quality of working life in Croatia deteriorated during the recession. The decline was mainly related to extrinsic job aspects such as adequate pay, fair pay, and job security. The most hardly hit by the recession were lower educated employees.